An exploratory study of search and information sharing behavior on Facebook - Santoso, Indriyani; Kurniawan, Rizal; Sartana; Suryani, Cahya (Universitas Mercu Buana Yogyakarta, 2023)
Individuals frequently seek information and then share that information. The research looks into the dynamics of these two behaviors on the social networking site Facebook. The study included 260 students, the average age of whom was 20. The Information Seeking in Facebook Scale (ISFS) categorizes information seeking behavior on Facebook into five types: social searches, social browsing, hedonic productivity, consumer trends, and general erudition. Meanwhile, students' information-sharing behavior was examined based on the frequency with which they shared information links via the Facebook network in the previous three months. The data obtained was analyzed using logistic regression. As a result, it was discovered that social search and social browsing are important types of information searches to determine the likelihood of someone sharing information. The findings of this study contribute to the flow of searching and sharing information, which can change thought patterns and attitudes and create behavior in the general public, particularly students. Keyword: Information search, information, Facebook, Information Search at Facebook Scale (ISFS)